Economic growth on islamic economic perspective: the effect of local income standard (PAD) and unemployment rate in Lampung province - Indonesia / Yakub Kuncara, Mardhiyah Hayati and Siska Yuli Anita - Kuncara, Yakub; Hayati, Mardhiyah; Yuli Anita, Siska (Universiti Teknologi Mara Selangor, 2023)
The purpose of this study was to find out local original income (PAD) and open unemployment rate (TPT) on the economic growth of districts and cities in Lampung province. To find out regional original income (PAD) and open unemployment rate (TPT) on the economic growth of districts and cities in Lampung province from an Islamic economic perspective. The method used in this study is a quantitative method using secondary data from the Official website of the Central Bureau of Statistics for Lampung Province, namely Regional Income Data, Open Unemployment Rate, and GRDP Per Capita at Constant Prices for 2017-2021. The results of the study show that Regional Original Income (PAD) and Open Unemployment Rate jointly affect the Economic Growth of Regencies and Cities in Lampung Province in 2017-2021